2015
DOI: 10.3389/fncir.2015.00031
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic deep brain stimulation reduces pathological information transmission to the thalamus in a rat model of parkinsonism

Abstract: The degeneration of dopaminergic neurons in the substantia nigra pars compacta leads to parkinsonian motor symptoms via changes in electrophysiological activity throughout the basal ganglia. High-frequency deep brain stimulation (DBS) partially treats these symptoms, but the mechanisms are unclear. We hypothesize that motor symptoms of Parkinson’s disease (PD) are associated with increased information transmission from basal ganglia output neurons to motor thalamus input neurons and that therapeutic DBS of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 58 publications
5
38
1
Order By: Relevance
“…In future work, we could explicitly model the afferent connections, but in that case these connections would participate in the network activity even in the absence of DBS, and would change the entire dynamics of the model. Furthermore, this effect reflects a hypothesis about subthalamic DBS, which proposes that it acts to replace pathological synchrony with low amplitude activity and regain information flow through the thalamus [5759]. Interestingly, while this hypothesis has been proposed for subthalamic DBS to treat Parkinson’s disease, our results indicate that a similar mechanism may apply for thalamic DBS for ET.…”
Section: Discussionsupporting
confidence: 79%
“…In future work, we could explicitly model the afferent connections, but in that case these connections would participate in the network activity even in the absence of DBS, and would change the entire dynamics of the model. Furthermore, this effect reflects a hypothesis about subthalamic DBS, which proposes that it acts to replace pathological synchrony with low amplitude activity and regain information flow through the thalamus [5759]. Interestingly, while this hypothesis has been proposed for subthalamic DBS to treat Parkinson’s disease, our results indicate that a similar mechanism may apply for thalamic DBS for ET.…”
Section: Discussionsupporting
confidence: 79%
“…Multiple other studies, however, have reported increased cGMP levels in the GPi [28] [29] [30] and in the SNr [30] during STN DBS suggesting increased levels of synaptic/metabolic activity consistent with activation of output from the stimulated structure. Regardless of whether one supports the inhibition or activation hypothesis, the far-reaching effect of DBS on other structures in the circuit is supported by a number of studies demonstrating alterations in cortical activity with STN [31] [32] or GPi DBS [33] as well as previous modeling [34,35] and animal studies recording from multiple structures in the circuit [9,24] [3638]. Changes in extracellular concentrations of striatal GABA and glutamate during STN stimulation lend further support to the varied and complex changes that occur during DBS [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…To shed light into the importance of basal ganglia activity changes for PD, models of parkinsonism are needed to investigate how this information transmission changes after dopamine depletion. We expect that the communication between basal ganglia and thalamus differs in parkinsonism and potentially more information is transmitted to thalamus than in the healthy situation [Reitsma et al, 2011, Anderson et al, 2015. In particular, we are curious how average noise correlations change and what happens to the coherence at high beta frequency (Fig.…”
Section: Gpi Vla Interneurons Vla Principal Neurons Striatummentioning
confidence: 99%
“…Most evidence comes from birds , and recently rodents [Anderson et al, 2015]. However, few data on the primate basal gangliathalamic connection is available [Kammermeier et al, 2014, Zimnik and.…”
Section: Gpi Vla Interneurons Vla Principal Neurons Striatummentioning
confidence: 99%
See 1 more Smart Citation